2023
DOI: 10.1177/14614448231161598
|View full text |Cite
|
Sign up to set email alerts
|

The psychological influence of dating app matches: The more matches the merrier?

Abstract: Swipe-based dating apps characteristically provide quantitative social feedback in the form of mattches. Surveys suggest a link between dating app success and well-being, but the nature of this correlation has yet to be examined. In an experiment with 125 undergraduate women, we manipulated dating app feedback: When accepting a profile, participants had either a high (27/31) or a low chance (3/31) of receiving matches. We found no effect of chance of matches on women’s loneliness or fear of being single. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 102 publications
0
2
0
1
Order By: Relevance
“…Questo comportamento genera una forma di gratificazione "in-app", che distoglie l'attenzione degli utenti dall'obiettivo principale, ovvero quello di instaurare connessioni significative con altri, indirizzando al contrario, l'attività dell'utente, verso l'accumulo di "match", quest'ultimi percepiti come fossero meri punteggi all'interno di un gioco. Alcuni studiosi, ispirandosi alla prospettiva psicoanalitica lacaniana, suggeriscono che le dating app sfruttano il desiderio degli utenti indirizzandolo verso l'app stessa tramite l'accumulo di "match" (Thomas et al, 2023a). Risultati di ricerca indicano che più della metà degli utenti non partecipa a incontri di persona, rimanendo all'interno dell'ambiente online (Thomas et al, 2023b).…”
Section: Gratificazione In-app E Compulsività Dello Swipeunclassified
“…Questo comportamento genera una forma di gratificazione "in-app", che distoglie l'attenzione degli utenti dall'obiettivo principale, ovvero quello di instaurare connessioni significative con altri, indirizzando al contrario, l'attività dell'utente, verso l'accumulo di "match", quest'ultimi percepiti come fossero meri punteggi all'interno di un gioco. Alcuni studiosi, ispirandosi alla prospettiva psicoanalitica lacaniana, suggeriscono che le dating app sfruttano il desiderio degli utenti indirizzandolo verso l'app stessa tramite l'accumulo di "match" (Thomas et al, 2023a). Risultati di ricerca indicano che più della metà degli utenti non partecipa a incontri di persona, rimanendo all'interno dell'ambiente online (Thomas et al, 2023b).…”
Section: Gratificazione In-app E Compulsività Dello Swipeunclassified
“…The positive reinforcement of social validation triggers the release of neurotransmitters in the brain, such as dopamine, which are associated with pleasure and reward (Dresp-Langley & Hutt, 2022). This neurological response reinforces the behavior of seeking validation, as individuals are motivated to replicate the experience of receiving positive feedback (Thomas et al, 2023). The pursuit of social validation becomes an integral part of their online presence and may drive individuals to carefully curate their content, seek attention, or engage in activities that are more likely to generate validation.…”
Section: Self-esteem and Self-worth In The Context Of Social Validationmentioning
confidence: 99%
“…5 According to the latest data I have obtained, the number of cases of dating violence among adolescents is always increasing and increasingly alarming (Meiksin et al, 2023;Petit et al, 2023). Some responses of young women admit to dating someone who always controls and manages them at all times (Thomas et al, 2023). Based on a survey conducted found that at least 1 in 10 senior high school students get violent dating treatment, including punches and slaps from their girlfriends and more than 8 million girls experience violence each year from their partners, who are typically teenagers (Baiden et al, 2021).…”
Section: Introductionmentioning
confidence: 99%